Water Level Modeling Based on Actual and Design Discharge in the Tabuk River Wetland Irrigation Area Using HEC-RAS: Pemodelan Tinggi Muka Air Berdasarkan Debit Aktual Dan Rancangan Pada Daerah Irigasi Rawa Sungai Tabuk Menggunakan HEC-RAS - Nilna Amal; Muhammad Rizky Firdaus (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
Wetland irrigation areas require good monitoring of discharge and water levels. Water level analysis can be done using software, for example, HEC RAS. The research analyzes the actual discharge and water surface elevation in the Tabuk River Irrigation Wetland Area. The data analysis process includes hydrological and hydraulic analysis. The research uses geometric ditch data as primary data, including channel cross-section and channel velocity. Daily rainfall is used as secondary data to analyze the hydrology part. Simulation results using steady flow conditions show variations in water level at each measurement station. The simulated water level is close to existing conditions at STA 0+500 and STA 1+500, with 15% and 17% error values, respectively. However, at STA 0+000 and STA 1+000, there are significant differences with differences of up to 70% and 160%. The significantly different results could be due to the influence of the accuracy of the channel geometry data